Environmental Education : Content Analysis of the Primary School World Knowledge Textbooks in Azerbaijan - Ahmadzada, Elnura (ADA University, 2020)
The protection of the nature and environment is considered as one of the priority issues all around the globe. However, weak public awareness hinders the protection of the nature and environment. To protect both, environmental education is taught at a very young age to bring up responsible citizens not only in the world but also in Azerbaijan. The main purpose of the study was to conduct content analysis on the primary school World Knowledge textbooks’ topics on environmental education. The second aim of the study was to explore to what extent the primary school World Knowledge textbooks’ topics on environmental education cover Palmer’s (1998) education about, in, and for the environment model and reflect Taylor’s (2011) environmental ethics and Mark’s (1844) human-nature relationship dimensions. Finally, the study aimed to understand stakeholders’ (a curriculum expert, a textbook author and a 2nd grade school teacher) perceptions and experiences about the primary school World Knowledge textbooks’ topics on environmental education and to what extent their perceptions and experiences coincide with Palmer's (1998) education about, in, for environment model, Taylor's (2011) environmental ethics, and Marx's (1844) human nature relationship dimensions. This study employed qualitative content analysis and qualitative interview approach to explore three stakeholders’ (acurriculum expert, a textbook author and 2nd grade school teacher) perceptions and experiences about the primary school World Knowledge textbooks’ topics on environmental education. The major finding of the content analysis was that the primary school World Knowledge textbooks comprised Palmer’s (1998) education about, in, for environment model’s first component about, which was a basic knowledge about environment. The second component in, which was raising awareness, and the third component for, which was action, was covered less than knowledge. Thus, the primary school World Knowledge textbooks’ topics on environmental education did not equally incorporate Taylor’s (2011) environmental ethics and Marx’s (1844) human nature relationship dimensions in comparison to knowledge. Similarly, the primary school World Knowledge textbooks’ topics on environmental education did not promote student engagement in activities related to the nature and environment. The significant finding of the interview data analysis was poor communication among three stakeholders (a curriculum expert, a textbook author, and 2nd grade school teacher). This study suggested that the primary school World Knowledge textbooks’ topics on environmental education should be more action-oriented. Besides, they should teach environmental ethics and human nature relationship more deeply.
Keywords: Education; Environmental education -- Azerbaijan.; Environmental ethics -- Azerbaijan.; Primary School -- Azerbaijan.